2014
DOI: 10.1016/j.brat.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Elevated reward-related neural activation as a unique biological marker of bipolar disorder: Assessment and treatment implications

Abstract: Growing evidence indicates that risk for bipolar disorder is characterized by elevated activation in a fronto-striatal reward neural circuit involving the ventral striatum and orbitofrontal cortex, among other regions. It is proposed that individuals with abnormally elevated reward-related neural activation are at risk for experiencing an excessive increase in approach-related motivation during life events involving rewards or goal striving and attainment. In the extreme, this increase in motivation is reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 202 publications
(292 reference statements)
7
75
1
Order By: Relevance
“…Given the differences between our paradigm and that of Chase et al (2013), the findings are not necessarily conflicting. However, in light of recent findings that indicate state-independent elevated striatal activity (Nusslock et al, 2014), but other researchers reporting results in the opposite direction (Trost et al, 2014), it seems to be important to separate the investigation of reward anticipation and reward outcome processing to gain a clearer picture in future studies.…”
Section: Reward Processing In Ud and Bdmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the differences between our paradigm and that of Chase et al (2013), the findings are not necessarily conflicting. However, in light of recent findings that indicate state-independent elevated striatal activity (Nusslock et al, 2014), but other researchers reporting results in the opposite direction (Trost et al, 2014), it seems to be important to separate the investigation of reward anticipation and reward outcome processing to gain a clearer picture in future studies.…”
Section: Reward Processing In Ud and Bdmentioning
confidence: 99%
“…Studies in BD reported more heterogeneous results, probably because of a higher variation of mood states. A recent review by Nusslock et al (2014) suggested increased NAcc responsiveness across all mood states in BD. However, not all available data support this notion.…”
Section: Introductionmentioning
confidence: 99%
“…41 Excessive activation of this neural circuit has been implicated in BD. 42 Using fMRI, one study reported elevated activation of the left lateral orbital frontal cortex (OFC; BA11/47) in patients with BD assessed during the manic …”
Section: Reward-related Neural Activation As Biological Marker In Bdmentioning
confidence: 99%
“…43 Increased OFC and ventral striatal responses during reward anticipation were also found in a subset of euthymic patients compared with non-psychiatric controls, suggesting that reward activation is not state-dependent. 42 Increased left frontal cortical activity is supported by electroencephalographic (EEG) assessment -a neurophysiological index of reward sensitivity -in individuals susceptible to bipolar spectrum diagnosis. 44 Another neurophysiological index is event-related potential (ERP), which is used to examine neuronal responses to feedback (feedback-related negativity [FRN]).…”
mentioning
confidence: 99%
See 1 more Smart Citation